2021
DOI: 10.1073/pnas.2104013118
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dot1L and H3K79 methylation in regulating somatic hypermutation of immunoglobulin genes

Abstract: Somatic hypermutation (SHM) and class-switch recombination (CSR) of the immunoglobulin (Ig) genes allow B cells to make antibodies that protect us against a wide variety of pathogens. SHM is mediated by activation-induced deaminase (AID), occurs at a million times higher frequency than other mutations in the mammalian genome, and is largely restricted to the variable (V) and switch (S) regions of Ig genes. Using the Ramos human Burkitt’s lymphoma cell line, we find that H3K79me2/3 and its methyltransferase Dot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 70 publications
(109 reference statements)
4
17
0
Order By: Relevance
“…S2F-S2H). The increase in H3K79me1 in the V region but not the C region with inhibitor treatment was reported in our previous paper (Duan et al, 2021). We found that the EPZ004777 treatment significantly but very slightly decreased the abundance of dCas9-APEX on chromatin in C-gRNA cells after the inhibitor treatment (Fig.…”
Section: Identification Of Proteins That Are Significantly Changed On...supporting
confidence: 85%
See 3 more Smart Citations
“…S2F-S2H). The increase in H3K79me1 in the V region but not the C region with inhibitor treatment was reported in our previous paper (Duan et al, 2021). We found that the EPZ004777 treatment significantly but very slightly decreased the abundance of dCas9-APEX on chromatin in C-gRNA cells after the inhibitor treatment (Fig.…”
Section: Identification Of Proteins That Are Significantly Changed On...supporting
confidence: 85%
“…Encouragingly, the abundance of MLLT1, a component of super elongation complex, was increased on V region after Dot1L inhibitor treatment. We had shown previously that the Dot1L inhibitor EPZ004777 only inhibited its enzymatic activity but did not change its physical abundance on the V region, and the EPZ004777 treatment only decreased the SHM by 30% compared with the 70% decrease of SHM in Dot1L KO cells (Duan et al, 2021). The Dot1L molecule has been shown to both form its own complex and to be a component of SEC where its function appears to be independent of its histone methyltransferase activity (Cao et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…SHM has also been correlated with the epigenetic landscape especially with activating histone marks. In particular, depletion of histone modifying enzymes resulted in decreased SHM and/or CSR accompanied with a decrease in activating histone modifications (24,(28)(29)(30)(31)(32)(33)(34)(35)(36). However, the precise role of these marks in SHM is unknown.…”
Section: Introductionmentioning
confidence: 99%